RETRACTED : The Effect of Job Satisfaction, Work Motivation, Work Environment, and Training on Employee Productivity at PT. Wijaya Karya Beton Tbk in East Jakarta - Muhammad Reza Pahlevi; Kumba Digdowiseiso (Journal of Social Science)
This research partially aims to analyze the effect of job satisfaction, work motivation, work environment, and training on the work productivity of operating bureau employees at PT. Wijaya Karya Beton Tbk. The population in this study were all employees of the operating bureau of PT. Wijaya Karya Beton Tbk, amounting to 285 employees. Determination of the sample using probability sampling method with sampling techniques using simple random sampling, then the size of the sample in this study were 166 respondents. The data analysis method in this research is multiple regression with the help of SPSS version 24.00. The results in this study indicate that partially the influence between job satisfaction, motivation, work environment and training has a positive effect on employee work productivity.